The universal non-neuronal nature of Parkinson's disease: A theory - Valente,André; Adilbayeva,Altynay; Tokay,Tursonjan; Rizvanov,Albert (PeerJ Preprints, 2016)
Parkinson's disease (PD) is one of the most common neurodegenerative disorders, yet the etiology of themajority of its cases remains unknown. In here, relevant published evidence is interpreted and integrated into a comprehensive hypothesis on the nature, origin and inter-cellular mode of propagation of sporadic PD. We propose to characterize sporadic PD as a pathological deviation in the global gene expression program of a cell: the PD expression-state, or PD-state for short.A universal cell-generic state, the PD-state deviation would be particularly damaging in a neuronal context, ultimately leading to neuron death and the ensuing observed clinical signs. We review why age accumulated damage caused by oxidative stress in mitochondria could be the trigger for a primordial cell to shift to the PD-state. We put forward hematopoietic cells could be the first to acquire the PD-state, at hematopoiesis, from the disruption in reactive oxygen species (ROS) homeostasis that arises with age in the hematopoietic stem-cell niche. We argue why, nonetheless, a cell ageing process is unlikely to explain the shift to the PD-state of all the subsequently affected cells in a patient, thus indicating the existence of a distinct mechanism of cellular propagation of the PD-state. We highlight recent findings on the intercellular exchange of mitochondrial DNA and the ability of mitochondrial DNA to modulate the cellular global gene expression state and propose this could form the basis for the intercellular propagation of the PD-state.
Keywords: Parkinsons disease; Neurodegenerative diseases; Mitochondria; Parkinson's disease; Neurodegeneration